Primates, Hominids, and Humans—from Species Specificity to Human Uniqueness? A Response to Barbara J. King, Gregory R. Peterson, Wesley J. Wildman, and Nancy R. Howell - Van Huyssteen, J. Wentzel (Zygon, 2008)
Abstract. In this response to essays by Barbara J. King, Gregory R. Peterson, Wesley J. Wildman, and Nancy R. Howell, I present arguments to counter some of the exciting and challenging questions from my colleagues. I take the opportunity to restate my argument for an interdisciplinary public theology, and by further developing the notion of transversality I argue for the specificity of the emerging theological dialogue with paleoanthropology and primatology. By arguing for a hermeneutics of the body, I respond to criticism of my notion of human uniqueness and argue for strong evolutionary continuities, as well as significant discontinuities, between primates, humans, and other hominids. In addition, I answer critical questions about theological methodology and argue how the notion of human uniqueness, theologically restated as the image of God, is enriched by transversally appropriating scientific notions of species specificity and embodied personhood.